2019
DOI: 10.1002/stc.2496
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive alleviation technique for optical‐turbulence‐induced errors in vision‐based displacement measurement

Abstract: Computer vision-based displacement measurement techniques can be affected by the optical turbulence in the field in hot weather. The optical turbulence can be observed naturally when viewing a thick layer of heated air. The nonuniform density distribution of the air due to heat creates spatial variations in refraction indexes, resulting in distortions in video images and measurement errors in displacements obtained from distorted videos. The effect of optical turbulence on vision-based displacement sensing is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The air convection leads to changes in the air's refractive index, which brings about the blurring effect. The image distortion induced by the atmospheric turbulence is beyond the scope of this study, interested readers are referred to Anantrasirichai et al 44 and Luo et al 45 For the thermal‐induced image drift, it has been shown to be insensitive to the camera orientation. However, it is worth stating that the differences in the camera orientations considered in this study are not extremely large.…”
Section: Discussionmentioning
confidence: 99%
“…The air convection leads to changes in the air's refractive index, which brings about the blurring effect. The image distortion induced by the atmospheric turbulence is beyond the scope of this study, interested readers are referred to Anantrasirichai et al 44 and Luo et al 45 For the thermal‐induced image drift, it has been shown to be insensitive to the camera orientation. However, it is worth stating that the differences in the camera orientations considered in this study are not extremely large.…”
Section: Discussionmentioning
confidence: 99%
“…The optical-turbulence effect can twist the measured target in the image and influence the image quality and motion tracking. Luo et al 230 investigated the motion behaviors of the background reference points induced by optical-turbulence effect by using statistical approaches and based on the observed statistical model, they eliminated the measurement errors of a long-span bridge under the influence of optical-turbulence effect. This technique is very promising and further investigation is necessary to validate the general applicability in different environmental application scenarios.…”
Section: Challenge and Opportunities In Real-life Practices Of Cv-shmmentioning
confidence: 99%
“…DIC has been implemented on actual bridges in several studies addressing the issues of real-time performance, image degradation from optical turbulence, and subpixel accuracy [ 36 , 37 , 38 ]. Such implementation has yet to consider moving traffic and address the inaccuracy due to imprecise synchronization of multiple cameras [ 39 ].…”
Section: Related Workmentioning
confidence: 99%